Processo de inclusão de crianças com necessidades especiais de saúde na escola: perspectiva de professores - Nascimento, Francisco Junio do (2024)
This is a study with a qualitative approach that aimed to understand the perception of teachers regarding the inclusion of children with special health needs in the school context. Semi-structured interviews were carried out with 22 teachers from public municipal schools in the interior of Rio Grande do Sul. The data obtained was subjected to inductive thematic analysis. Ethical aspects were respected, and the project was approved by the institution's Research Ethics Committee. The results demonstrated the need for greater theoretical and technical support to assist teachers in the process of including children with special health needs in the school environment. In addition to the fragility of qualified human resources, especially monitors, who assist students in social interactions, teaching in general and teaching applications in the classroom. Teachers feel frustrated and overwhelmed and would like to have a greater partnership with the health sector in the process of including these children in the school environment. As strategies for this inclusion, teachers cited: differentiated planning of activities, inclusion with other colleagues in recreational activities and planning together with special educators as well as exchange of knowledge between colleagues in the education network. Professionals feel the need for continued training for the inclusion process of these children and pointed to the nursing professional as a possible trainer/facilitator for this process. It is concluded that the teachers' perception regarding the inclusion of these children permeates the difficulties related to the child, the training process and institutional and infrastructure. They suggest bringing the education and health sectors closer together so that teachers feel more empowered in the classroom with these children, so they can carry out their activities with quality and with the support they need.